2004
DOI: 10.1038/ng1358
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GALNT3, encoding a protein involved in O-linked glycosylation, cause familial tumoral calcinosis

Abstract: Familial tumoral calcinosis (FTC; OMIM 211900) is a severe autosomal recessive metabolic disorder that manifests with hyperphosphatemia and massive calcium deposits in the skin and subcutaneous tissues. Using linkage analysis, we mapped the gene underlying FTC to 2q24-q31. This region includes the gene GALNT3, which encodes a glycosyltransferase responsible for initiating mucin-type O-glycosylation. Sequence analysis of GALNT3 identified biallelic deleterious mutations in all individuals with FTC, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
358
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 535 publications
(375 citation statements)
references
References 16 publications
11
358
1
5
Order By: Relevance
“…The existence of various trade routes between Africa and the Middle East during many centuries has been invoked to explain the peculiar geographical distribution of FTC. However, different HFTC-causing mutations have been identified in African-American and Middle Eastern patients (Topaz et al 2004). In the present report, we describe the identification of a novel GALNT3 mutation in a patient of European extraction with features typical of HFTC, demonstrating the existence of GALNT3 mutations outside the Middle Eastern and African populations.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The existence of various trade routes between Africa and the Middle East during many centuries has been invoked to explain the peculiar geographical distribution of FTC. However, different HFTC-causing mutations have been identified in African-American and Middle Eastern patients (Topaz et al 2004). In the present report, we describe the identification of a novel GALNT3 mutation in a patient of European extraction with features typical of HFTC, demonstrating the existence of GALNT3 mutations outside the Middle Eastern and African populations.…”
Section: Introductionmentioning
confidence: 55%
“…It is often associated with hyperphosphatemia (Smack et al 1996), and is then termed hyperphosphatemic familial tumoral calcinosis (HFTC; MIM211900). HFTC has been shown to result from loss-of-function mutations in at least two genes: GAL-NT3 coding for UDP-N-acetyl-alpha-D-galactosamine: polypeptide n-acetylgalactosaminyltransferase 3 (ppGalNacT3) (Topaz et al 2004;Ichikawa et al 2005), a glycosyltransferase, which initiates O-glycosylation (Ten Hagen et al 2003);and FGF23 (Benet-Page`s et al 2005;Larsson et al 2005;Araya et al 2005;Chefetz et al 2005) coding for fibroblast growth factor 23 (FGF23), a potent phosphaturic protein (Berndt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(12) FTC and HHS can result from homozygous mutations in the O-linked glycosyl transferase N-acetylgalactosaminyltransferase 3 (ppGalNAcT3), a member of the galactosaminyl transferase family that is known to transfer N-acetylgalactomine residues to specific serine/threonine residues. (13) It has been shown that mutations in ppGalNAcT3 lead to a loss of FGF23 glycosylation and enhanced cleavage of FGF23, resulting in very low levels of iFGF23 and correspondingly high cFGF23 levels. (14) On the other hand, patients with ADHR who carry mutations in FGF23 within the conserved furin cleavage motif, 176 RHTR 179 , (15,16) have elevated blood iFGF23 levels.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that patients with tumoral calcinosis have elevated concentrations of FGF-23 measured by an assay that detects carboxyl terminal fragments of FGF-23 [17,29]. In contrast, these patients have normal or low-normal concentrations of intact FGF-23.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the gene alter the furin proconvertase recognition site (176RHTR179) in the protein such that the arginine residue at 176 is replaced by glutamine (R176Q) or the arginine residue at amino acid 179 is replaced by a glutamine (R179Q) or tryptophan residue (R179W). In contrast, individuals with tumoral calcinosis have elevated serum phosphate levels and elevated serum levels of the FGF-23 carboxyl terminal fragments [17,29]. Shimada et al have tested the bioactivity of a biosynthetic carboxyl terminal fragment of FGF-23 (aa 180-251) and an N-terminal fragment of FGF-23 and have shown that in contrast to the phosphaturic action of the full-length protein, these peptides fragments are biologically inactive 24 hours after their administration intraperitoneally to mice [11] at a dose of 5 g per mouse every 12 hours.…”
Section: Introductionmentioning
confidence: 99%